Geology the Eisenbrey Zn-Cu-Pb Deposit, Rusk County, WI - Jackson, Nathaniel R.; De Moura Merss, Bruno Henrique; Lodge, Robert W.D. (My University, 2017)
The primary objective of this project is to complete a geochemical and petrographic study of the poorly understood Zn-Pb-Cu mineralization of the Eisenbrey deposit hosted in Precambrian volcanic assemblages (DeMatties, 1994) of the Penokean Orogen. These deposits and their regional geological and economic significance have not been examined in any detail, despite almost 20 years of advancement in the fields of economic and Precambrian geology. Mapping efforts after the discovery of massive sulfide bodies elsewhere in the Penokean Orogen resulted in the 1970 discovery of an outcropping iron formation with anomalous base metal concentrations on the banks of the Thornapple River just 4 miles away from the Flambeau Cu-Au mine near Ladysmith, WI. Complete characterization of this ore body ceased because of the controversy surrounding the extraction of metallic sulfide ore bodies in the state.
Color poster with text, charts, images, maps and diagrams.
Keywords: Subsurface geology; Geology; Rusk County (Wis.); Posters